Development of Ozone Generator Mini with DDBD (Double Dielectric Barrier Discharge) Technology at Atmospheric Air Pressure - Agus Sudarmanto; Eko Yulianto; Muhammad Nur (Department of Physics, Sebelas Maret University, 2024)
Pesticide residues in fruits and vegetables pose a danger to human health if consumed for a certain period. This requires appropriate technology for household scale and is environmentally friendly. Ozone is a strong oxidizing agent capable of degrading pesticide residues in fruits and vegetables. Ozone is a green chemical compound because it does not produce harmful derivative compounds, and is even friendly to the environment. The development of a mini ozone generator with DBD technology has been successfully carried out. The DDBD reactor is made of Pyrex glass with a length of 10 cm and an outer diameter of 4 cm. The reactor uses electrodes made of copper plates. The outer electrode is 13 cm long and 5 cm wide, while the inner electrode is 10 cm long and 5 cm wide. Optimization of the mini ozone generator is carried out using high voltage AC pulses whose pulse frequency can be varied from 30 to 60 Hz with 10 Hz intervals. The free air flow rate was varied at 0.2 – 0.8 lpm with an interval of 0.2 lpm. The optimum ozone production of 480 mg/l was obtained at a voltage setting of 2.8 kV and a frequency of 50 Hz and a flow rate of 0.2 lpm. In this setting, the DDBD reactor consumes 9.32 watts of power. The development of mini ozone generator technology has the potential to be applied on a household scale because of the small reactor size and low power consumption.